Do longitudinal studies support long-term relationships between aggressive game play and youth aggressive behaviour? A meta-analytic examination. Issue 7 (22nd July 2020) - Drummond, Aaron; Sauer, James D.; Ferguson, Christopher J.
Abstract : Whether video games with aggressive content contribute to aggressive behaviour in youth has been a matter of contention for decades. Recent re-evaluation of experimental evidence suggests that the literature suffers from publication bias, and that experimental studies are unable to demonstrate compelling short-term effects of aggressive game content on aggression. Long-term effects may still be plausible, if less-systematic short-term effects accumulate into systematic effects over time. However, longitudinal studies vary considerably in regard to whether they indicate long-term effects or not, and few analyses have considered what methodological factors may explain this heterogeneity in outcomes. The current meta-analysis included 28 independent samples including approximately 21 000 youth. Results revealed an overall effect size for this population of studies ( r = 0.059) with no evidence of publication bias. Effect sizes were smaller for longer longitudinal periods, calling into question theories of accumulated effects, and effect sizes were lower for better-designed studies and those with less evidence for researcher expectancy effects. In exploratory analyses, studies with more best practices were statistically indistinguishable from zero ( r = 0.012, 95% confidence interval: −0.010, 0.034). Overall, longitudinal studies do not appear to support substantive long-term links between aggressive game content and youth aggression. Correlations between aggressive game content and youth aggression appear better explained by methodological weaknesses and researcher expectancy effects than true effects in the real world.